Critical theory a very short introduction - Bronner, Stephen Eric, 1949- (New York ; Oxford : Oxford University Press, 2011)
In this volume, Stephen Eric Bronner provides sketches of famous and less famous representatives of the critical tradition (such as George Lukacs and Ernst Bloch, Theodor Adorno and Walter Benjamin, Herbert Marcuse and Jurgen Habermas) as well as many of its seminal texts and empirical investigations.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Critical theory